Narrative Counter-Terror: Deconstruction, Deliverance, and Debilitation - McGregor, Rafe (Terrorism and political violence, 2022)
The aim of this article is to explore and evaluate narrative analysis as a counter-terror strategy. Research has demonstrated that both the white supremacist and Muslim fundamentalist calls to global violence are instantiations of a single master narrative, victim, which commits the ingroup to the restoration of utopia by the expulsion or extermination of the outgroup. This study deconstructs texts from American Renaissance and Rumiyah to show that the victim master narrative is underpinned by the concept of deliverance, which combines the desirability of the survival of the ingroup (with its various superior qualities) and the likelihood of destruction by the outgroup (with its vastly superior numbers) to justify resistance, defense, and attack. The expanded and elaborated master narrative is then assessed in terms of its potential to: (1) debilitate extremist recruitment; and (2) transform attempts to reduce global terrorism by providing a soft-power alternative to the unsuccessful hard-power strategies that have characterized twenty-first century counter-terror thus far.